PRESERVING THE TRADITION OF HADITH SANAD IJAZAH IN PESANTREN OF MANDAILING NATAL: Scholarly Continuity and Academic Challenges - Siregar, Ilham Ramadan; Ritonga, Raja; Hamid, Asrul; Hsb, Zuhdi; Nst, Andri Muda; Rababah, Mahmoud Ali (RIWAYAH, 2025)
The sanad tradition serves as a fundamental mechanism for preserving the authenticity and continuity of hadith through a reliable and accountable chain of transmission. In Indonesia, particularly in Mandailing Natal, this tradition is actively maintained in Pesantren (pesantren), where the transmission of canonical hadith texts—such as Arba‘in an-Nawawi, Bulugh al-Maram, and Sahih al-Bukhari—relies on a sanad-based educational system. This study explores the mechanism of granting ijazah sanad (sanad certificates) in selected pesantren—notably Musthafawiyah, Darul Ulum, and Roihanul Jannah—and examines their contribution to sustaining hadith scholarship. Employing a qualitative methodology that includes fieldwork and historical analysis, the research reveals that sanad certification is not a mere formal acknowledgment, but the result of a rigorous academic and spiritual process. Teaching methods such as musyafahah, talaqqi, and sorogan are employed alongside recitations in class, mosques, and during Ramadan. Certificates are granted only to students who meet strict academic criteria, including completion of hadith study under a teacher with authenticated sanad lineage, comprehension of the matan, and observance of proper adab. Most sanad lineages trace back to scholars connected to Madrasah Ash-Shalatiyah and Darul Ulum Makkah, including Shaykh Muhammad Yasin al-Fadani. Despite its critical role, academic studies on hadith sanad remain limited compared to Qur’anic sanad research. This study underscores the need to revitalize scholarly attention to hadith sanad traditions and affirms the strategic role of pesantren as institutions preserving the integrity and transmission of classical Islamic knowledge. [Tradisi sanad merupakan mekanisme fundamental dalam menjaga keautentikan dan kesinambungan hadis melalui rantai transmisi yang andal dan dapat dipertanggungjawabkan. Di Indonesia, khususnya di Mandailing Natal, tradisi ini secara aktif dilestarikan di lembaga pendidikan pesantren, di mana transmisi kitab-kitab hadis klasik seperti Arba‘in an-Nawawi, Bulugh al-Maram, dan Sahih al-Bukhari dilakukan melalui sistem pendidikan berbasis sanad. Penelitian ini mengkaji mekanisme pemberian ijazah sanad (sertifikat sanad) di beberapa pesantren—terutama Musthafawiyah, Darul Ulum, dan Roihanul Jannah—dan menelaah kontribusinya dalam mempertahankan keberlanjutan keilmuan hadis. Dengan pendekatan kualitatif melalui studi lapangan dan analisis historis, penelitian ini menemukan bahwa pemberian ijazah sanad bukan sekadar formalitas, melainkan hasil dari proses akademik dan spiritual yang ketat. Metode pengajaran seperti musyafahah, talaqqi, dan sorogan diterapkan bersamaan dengan pengajian di kelas, masjid, dan selama bulan Ramadan. Sertifikat hanya diberikan kepada santri yang memenuhi kriteria akademik ketat, termasuk menyelesaikan kajian kitab hadis di bawah bimbingan guru bersanad sah, memahami matan hadis, dan menunjukkan adab serta komitmen belajar. Mayoritas rantai sanad ditelusuri hingga ulama-ulama yang terhubung dengan Madrasah Ash-Shalatiyah dan Darul Ulum Makkah, termasuk Syekh Muhammad Yasin al-Fadani. Meskipun memiliki peran krusial, kajian akademik tentang sanad hadis masih terbatas dibandingkan dengan kajian sanad Al-Qur’an. Studi ini menegaskan pentingnya revitalisasi perhatian akademik terhadap tradisi sanad hadis dan meneguhkan peran strategis pesantren dalam menjaga integritas dan transmisi keilmuan Islam klasik.]